Error propagation in open respirometric assays - Lobo, Cintia Cecilia (2014)
This work deals with the calculation of the uncertainty of the exogenous respiration rate (Rex) and the total oxygen consumed (OCT) derived from a single open respirometric profile. Uncertainties were evaluated by applying a linear error propagation method. Results show that standard deviations (SD) of Rex and OCT depend not only on the SD of the dissolved oxygen (C) and kLa (kLa), but also on the SD of the derivative term (dC/dt) of the oxygen mass balance equation (b). A Monte Carlo technique was employed to assess b; a power law expression for the dependence of sb as a function of sC, the time window (tw) and the sampling rate (δt) was proposed. The equations obtained in the present work are useful to calculate suitable conditions (e.g., biomass concentration, kLa) that minimize the coefficient of variation corresponding to Rex and OCT.